Clinical background affecting pregnancy outcome following local endometrial injury in infertile patients with repeated implantation failure. (2nd July 2016) - Kitaya, Kotaro; Matsubayashi, Hidehiko; Takaya, Yukiko; Nishiyama, Rie; Yamaguchi, Kohei; Ishikawa, Tomomoto
Abstract: Local endometrial injury (LEI) has been performed as a promising medical intervention to improve the pregnancy outcome in infertile women suffering from repeated implantation failure (RIF) in in vitro fertilization-embryo transfer cycles. The effect of LEI, however, remains controversial. The aim of this retrospective study was to identify the subgroups of patients with RIF who benefit from LEI. We compared the clinical parameters between the patients who had had a clinical pregnancy in the subsequent embryo transfer cycle following the LEI cycle (LEI-CP group, n  = 94) and those who had resulted in negative pregnancy test (LEI-NP group, n  = 114). The female age, basal follicle stimulating hormone concentration, number of past oocyte pickup cycles, and embryos/blastocysts transferred in the past three RIF cycles were significantly ( p  < 0.047) lower in the LEI-CP group than the LEI-NP group. The prevalence of polycystic ovarian syndrome was significantly ( p  = 0.0059) higher in the LEI-CP group than in the LEI-NP group. These findings suggest that LEI is most effective to improve the pregnancy outcome in patients undergoing RIF with uncompromised ovarian reserve, particularly in those with polycystic ovarian syndrome.